2020
DOI: 10.1007/s10708-020-10184-6
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer geographic information in the Global South: barriers to local implementation of mapping projects across Africa

Abstract: The world is awash in data-by 2020 it is expected that there will be approximately 40 trillion gigabytes of data in existence, with that number doubling every 2 to 3 years. However, data production is not equal in all places-the global data landscape remains heavily concentrated on English-speaking, urban, and relatively affluent locations within the Global North. This inequality can contribute to new forms of digital and data colonialism. One partial solution to these issues may come in the form of crowdsourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 64 publications
0
17
0
2
Order By: Relevance
“…Although the Champions were financially compensated in this project and reported mutual benefits, their proven value leaves critical questions about the nature of labor in crowdsourcing and in the Global South, as well as long-term sustainability. Such questions are beyond the scope of this article, but our other reflections on this project (see Young et al, 2020) engage similar critical questions.…”
Section: Discussionmentioning
confidence: 90%
“…Although the Champions were financially compensated in this project and reported mutual benefits, their proven value leaves critical questions about the nature of labor in crowdsourcing and in the Global South, as well as long-term sustainability. Such questions are beyond the scope of this article, but our other reflections on this project (see Young et al, 2020) engage similar critical questions.…”
Section: Discussionmentioning
confidence: 90%
“…This project, called Advancing Library Visibility in Africa (ALVA), broadly examines the relationship between public libraries and sustainable development across sub-Saharan Africa. Other components of the project have focused on understanding and building the capacity of African library systems to collect and share data generally (e.g., Lynch et al 2020aLynch et al , 2020bLynch et al , 2020cYoung et al 2020). In contrast, this paper draws on a set of interviews with development practitioners about what types of data libraries were most persuasive in driving their decision-making around partnerships.…”
Section: Methodsmentioning
confidence: 99%
“…[…] I literally don't know the landscape." While it is certainly possible that libraries do not exist within particular communities in which our participants have done work, our project has mapped a fairly dense network of libraries across the continent (e.g., Young et al 2020). Furthermore, one of our participants that does advocacy for libraries within the development context indicated that they regularly have to counter the argument that libraries do not exist.…”
Section: Current Perceptions Of Librariesmentioning
confidence: 99%
“…Sawaya et al (2011) recommend going further to combine "evidence from primary sources, including surveys and case studies, and secondary sources, such as government statistics and reports" (450) to comprehensively demonstrate how libraries contribute to funder goals. Young et al (2020) have pointed out that official sources may lack necessary data, however, and so recommend novel data collection methods such as crowdsourcing to counter this challenge and enable libraries in Africa to fill gaps in official data sets. Overall, Moahi (2019) asserts that using any data effectively requires both qualitative and quantitative data, and crucially, analytic skills in order to weave together a convincing story about the value of African libraries in development.…”
Section: African Libraries In Developmentmentioning
confidence: 99%
“…Libraries engaged in data collection could also leverage access to local populations as "places where a lot of people go" (Participant 5), given some organizations' interest in partners who serve specific populations such as women, youth, or refugees (4 participants). In this way, libraries could fill the gaps that exist in official data in order to furnish information development organizations want but find lacking in other official data sources, as African libraries have done via crowdsourced mapping (Lynch et al, 2020b;Young et al, 2020).…”
Section: Roles For Librariesmentioning
confidence: 99%